Trust: Theoretical Fundamentals and Role in Designing Sustainable Community Development - Kuzmuk, Olga M. (Baltija Publishing, 2024)
Theoretical and empirical research on trust has profound practical significance, as it allows us to understand the essence of institutional processes occurring in society. A high level of trust in political and administrative institutions can contribute to an increase in civic engagement, which, in turn, can constructively impact community development and promote its sustainable growth. The article investigates trust as a social phenomenon that has a significant influence on the sustainable development of communities. The purpose of the study is to explore the concept of «trust» through the lens of analyzing theoretical concepts of trust and examining its role in constructing and designing sustainable community development; analyzing the impact of trust on the implementation of sustainable development initiatives in communities. The methodology of the research includes the analysis of scientific sources, conducting empirical studies, as well as using qualitative and quantitative methods to assess the level of trust in communities. The study found that trust is an important factor that either facilitates or hinders the successful implementation of sustainable development projects. The results indicate that a high level of trust in society positively impacts citizen engagement in decision-making processes and the implementation of initiatives related to environmental, social, and economic aspects of development. Practical implications include a series of recommendations for local government bodies aimed at enhancing the transparency and openness of their actions, which, in turn, will contribute to strengthening trust within communities. The path of scientific inquiry into trust moves from understanding it as an element of interpersonal interaction in everyday life to grasping trust as social phenomenon, a significant social resource for society, which potentially has the capacity to substantially influence various areas of public life and positively impact community development. The value/originality lies in the fact that the topic of trust is extremely relevant, especially in the context of developing sustainable development strategies for local communities in Ukraine. The article examines the theoretical foundations of trust as an important social phenomenon that plays a key role in the processes of sustainable community development. It has been studied that trust is the foundation of social cohesion, which, in turn, contributes to the effective functioning of social institutions and encourages citizens to actively participate in community life. The author explores various dimensions of trust and analyzes the factors that influence its formation. It has been found that the level of trust in communities directly correlates with the success of implementing initiatives in the field of sustainable development, particularly social programs. The article also includes an analysis of existing approaches to studying trust in sociology, which allows for the identification of the most relevant aspects for practical application. Communication strategies play an important role in building trust, fostering openness and transparency in the actions of government bodies and local self-governments. Conclusions have been drawn that to achieve sustainable community development, it is necessary to actively work on increasing the level of trust in society, which includes educational programs, the implementation of mechanisms for citizen participation in decision-making, and the development of partnerships among various stakeholders.
Keywords: Trust; community development